Dictionaries Faced With a Nomination Conflict. An Analysis of the Semantic Modelling of the integration, insertion, assimilation, inclusion, acculturation, incorporation Paradigm in Two Universal French Language Dictionaries - Vadot, Maude (Kalbotyra, 2021)
This article aims to conduct a metalexicographical micro-analysis of a paradigm of French lexemes whose uses have raised socio-political issues for several decades: integration, insertion, assimilation, inclusion, even acculturation and incorporation. While many recent publications bring these terms into play as sociological concepts, or study their uses in political discourse, work on the semantic functioning and uses of these lexemes in other discourses is rarer. However, the recurrent nomination conflict that runs through French public policies on immigration shows that the stakes of these usages remain salient. Do French dictionaries make it possible to grasp the ideological issues raised by the competing uses of lexemes? How do they treat and model the abundance of uses of these lexemes? How are paradigmatic competitors related: opposition, contrast, synonymy, hyperonymy, co-hyponymy? What are the salient semantic features retained in the given definitions?The corpus selected for this study is composed of extracts from two generalist French-language dictionaries, the Petit Robert de la langue française and the Trésor de la Langue Française informatisé. I analyse the production of meaning at work by using a grid with four entries. First, I model and analyze the semantic relations established between the terms of the paradigm, relations which structure the paradigm. I then try to identify the semantic features which are similar or different between the lexemes, thus revealing another type of structure in the micro-system. Last, I work on the collocations and the agentive configurations implemented in the definitions and examples composing each article.All these analyses highlight a defining circularity that hinders a contrastive grasp of the lexemes, in a context where important social and political issues are at stake.
Keywords: lexicography; synonymy; contrastive meaning; French-language; integration; immigration